Cattle in the Anthropocene: Four propositions. Issue 1 (26th June 2017) - McGregor, Andrew; Houston, Donna
Abstract : The "Anthropocene", a proposed geological epoch in which humanity is positioned as the core driver of planetary change, is eliciting proposals oriented at reworking human–nature relations. The more common technoscientific responses call for more investment oriented at further controlling human and non‐human processes, whereas relational responses seek more convivial relations with non‐humans – recognising the diverse agencies present in more‐than‐human worlds. In this paper, we draw from the work of Bruno Latour to develop an approach oriented at identifying and assessing the composition and quality of propositions emerging in relation to the expanding planetary impacts of cattle industries. Four propositions are identified in the Australian context, variously promoting intensification, naturalisation, veganism and artificial beef and dairy production. The composition, agencies and resistances within each proposition are reviewed, as well as the overall quality of their articulation. We discuss each proposition by considering principles drawn from recent work on more‐than‐human geography and lively commodities – particularly the wild lives and world‐making liveliness of the human and non‐human actors involved. Our analysis shows that the most well‐funded and prominent proposition – based on an intensification of meat and dairy industries – reinforces existing human–nature dualisms and is oriented more at perpetuating existing political economies than providing an effective response to Anthropocene challenges. We argue that creative consumption‐oriented responses, which are able to think in the presence of human and non‐human others, are likely to provide more effective and lively ways of addressing planetary concerns.